CATIA core tools : computer aided three-dimensional interactive applications - Michaud, Michel , 1963- (McGraw-Hill, 2012)
"A practical guide to selecting and using CATIA toolsCATIA Core Tools: Computer Aided Three-Dimensional Interactive Applications covers this computer-aided 3D interactive application for high-end manufacturing environments. CATIA is a multi-platform application which includes CAD, CAM, and CNC applications all in one to achieve seamless transactions between applications. Dassault (creator of CATIA) releases a new edition twice a year. As most engineers do not need to know the hundreds of different applications that come with this software, this book offers the core topics in print and then allows you to download (for a fee) specialty tool(s). Specialty tools include: Solid Design / Assemblies / Surface Design / Aerospace Sheet Metal Design / Kinematics Calculations and Analysis / Composites Modeling / 3-axis NC Programming / 5-axis NC Programming / NC Turning / Knowledgeware / Stress Analysis.CATIA Core Tools: Computer Aided Three-Dimensional Interactive Applications Includes free downloadable AVI files Offers specialty tools for download (for a fee) Prepares you for the CATIA Certification exam Allows you to customize information/tools in accordance with your requirements "-- Provided by publisher